Motion Descriptions in English and Greek: A Cross-Typological Developmental Study of Conversations and Narratives - Selimis, Stathis; Katis, Demetra (Linguistik Online, 2010)
Theoretical claims about typologically constrained differences in how speakers habitually describe physical motion are tested through three cross-linguistic developmental studies. Three types of data are analyzed in Greek and English, languages here characterized respectively as Verb- and Satellite-framed in the coding of motion: spontaneous conversations between adults and children aged 1;8–4;6 as well as two types of narratives elicited through pictures and a film from 4-, 7-, 10-year olds and adults. Results show, on the one hand, largely predictable cross-linguistic differences, with overall greater attention paid to manner in English than in Greek and different patterns for coding path. On the other hand, the very appearance as well as intensity of typological effects also depend upon various interacting factors: the precise ways of measuring them, the age of speakers, type, content and communicative exigencies of the discourse as well as the detailed structural characteristics of a language.